2019
DOI: 10.1001/jamaneurol.2019.2214
|View full text |Cite
|
Sign up to set email alerts
|

Staging β-Amyloid Pathology With Amyloid Positron Emission Tomography

Abstract: IMPORTANCE Different brain regions appear to be involved during β-amyloid (Aβ) accumulation in Alzheimer disease (AD), but a longitudinally valid system to track Aβ stages in vivo using positron emission tomography (PET) is lacking. OBJECTIVE To construct a longitudinally valid in vivo staging system for AD using amyloid PET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

26
182
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 182 publications
(210 citation statements)
references
References 40 publications
26
182
2
Order By: Relevance
“…The results were also supported by our longitudinal progression analysis in completely amyloid-negative subjects at baseline, who after 2 years of follow-up displayed amyloid-positivity in the same anterior temporal lobe regions (corresponding to stage I of the cross-sectional staging scheme). Nonetheless, these results are in contrast with reports of early amyloid accumulation in anterior and posterior midline regions (Mattsson, Palmqvist, Stomrud, Vogel, & Hansson, 2019;Palmqvist et al, 2017;Villeneuve et al, 2015). Such differences can most likely…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…The results were also supported by our longitudinal progression analysis in completely amyloid-negative subjects at baseline, who after 2 years of follow-up displayed amyloid-positivity in the same anterior temporal lobe regions (corresponding to stage I of the cross-sectional staging scheme). Nonetheless, these results are in contrast with reports of early amyloid accumulation in anterior and posterior midline regions (Mattsson, Palmqvist, Stomrud, Vogel, & Hansson, 2019;Palmqvist et al, 2017;Villeneuve et al, 2015). Such differences can most likely…”
Section: Discussioncontrasting
confidence: 96%
“…Interestingly, a comparison of the evolution of mean regional SUVR values with the probabilistic information on regional amyloid-positivity in our longitudinal probabilistic model suggests that the observed regional onset of pathology does not coincide with fastest progression in amyloid accumulation ( Figure 5). Thus, SUVR values of the temporal regions identified to exhibit the first suprathreshold signal displayed only a rather moderate increase over the modeled time intervals, and were surpassed at later time points by the higher SUVR increases in AD-typical frontoparietal regions that were also consistently identified as fast accumulating regions in previous longitudinal amyloid-PET studies (Bilgel et al, 2016;Marinescu et al, 2019;Mattsson et al, 2019;Villain et al, 2012). Gonneaud et al (2017) suggested that the early signal increase in the temporal neocortex may be attributable to "physiologic" agerelated amyloid accumulation that occurs independently from ADrelated changes in the anterior and posterior midline regions.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This could for, example, also cause the initial increase in CSF NfL that is too subtle to be clinically relevant (early change point; Figs A and ), followed by a more marked change better corresponding to overt neurodegeneration (late change point; Figs A and ). This hypothesis is also in agreement with the contradictory studies showing that subtle longitudinal changes in NfL can be detected 16 years before the onset of cognitive symptoms (Preische et al , ), while cross‐sectional differences are only noticeable at the MCI and dementia stage (Mattsson et al , ,b).…”
Section: Discussionsupporting
confidence: 88%
“…The Ab40 finding should also be interpreted cautiously since this initial decline was driven by few individuals and the Ab40 model was barely significant for CSF (P = 0.02; Appendix Fig S1) and was not significant for plasma (P = 0.37; Appendix Fig S2). Even though there are previous studies supporting the use of CSF Ab42 measured in isolation to detect early Ab accumulation (Mattsson et al, 2015(Mattsson et al, , 2019bPalmqvist et al, 2016Palmqvist et al, , 2017, the ratio probably provides a more reliable measure of accumulating Ab fibrils and increases its specificity since Ab40 acts as a reference peptide that can, for example, account for inter-individual differences in CSF concentrations and differences in pre-analytical handling of the samples which otherwise may lead to falsepositive or false-negative results using just Ab42 (Janelidze et al, 2016;Lewczuk et al, 2017). Although the biomarkers for tau phosphorylation state (P-tau), synaptic dysfunction (neurogranin), glial activation and inflammation (YKL-40), and neurodegeneration (NfL and T-tau) changed after CSF Ab42, they still changed at a very early stage, just before or around the threshold for Ab PET positivity.…”
Section: Discussionmentioning
confidence: 99%